ANALYSIS OF ACCOUNTING SYSTEM IN SALES CV. DUTA JAVA TEA INDUSTRI (Tea 2Tang) TEGAL - One, Wahyuni; Isafaatun, SE., MM, Eliya; ekowati, SE., MM, Dhiana (Accounting, 2009)
The purpose of this study was to determine the accounting system cash sales that happened on the CV. Duta Java Tea Industri (2 Tang Tea). The problem in this research is "(1) how the implementation of Accounting System Sales in the Company CV. Duta Java Tea Industri, (2) Is Sales Accounting System which was held on the CV. Duta Java Tea Industri has been able to present the required information management company, (3) Does the Internal Control System has been implemented by the Company CV. Duta Java Tea Industri in the implementation of corporate Sales Accounting System. " The method and type of data used in data collection that is kind of secondary data consist of documentation methods and methods of theoretical basis. Technique or method of sampling in this study is the company CV. Duta Java Tea Industri with over 1-month observation period began on December 1 to December 25, 2008. While the data analysis techniques used include (1) descriptive: company profile, sales accounting system, accounting procedures within the system of cash sales. Test results on the CV. Duta Java Tea Industri show that has been operating efficiently. This can be seen from cash sales report showing the number of orders or an increase in demand by consumers. Keywords: Accounting System, Sales.